2006
DOI: 10.1158/1535-7163.mct-06-0185
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of biochemical and biological effects of ML858 (salinosporamide A) and bortezomib

Abstract: Strains within the genus Salinospora have been shown to produce complex natural products having antibiotic and antiproliferative activities. The biochemical basis for the cytotoxic effects of salinosporamide A has been linked to its ability to inhibit the proteasome. Synthetically accessible salinosporamide A (ML858) was used to determine its biochemical and biological activities and to compare its effects with those of bortezomib. ML858 and bortezomib show time-and concentration-dependent inhibition of the pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 42 publications
6
63
0
Order By: Relevance
“…Both NPI-0052 and bortezomib have been reported to exhibit time and concentration-dependent inhibition of the proteasome in vitro based on their different kinetics and pharmacologic profiles (58). With respect to the efficacy of each agent to induce tumor cell sensitization to TRAIL, bortezomib has been shown to be effective at concentrations ranging from 0.5 M up to 10 M in various tumor models including ovarian, thyroid, colon, and pancreatic carcinomas (38 -40, 59).…”
Section: Discussionmentioning
confidence: 99%
“…Both NPI-0052 and bortezomib have been reported to exhibit time and concentration-dependent inhibition of the proteasome in vitro based on their different kinetics and pharmacologic profiles (58). With respect to the efficacy of each agent to induce tumor cell sensitization to TRAIL, bortezomib has been shown to be effective at concentrations ranging from 0.5 M up to 10 M in various tumor models including ovarian, thyroid, colon, and pancreatic carcinomas (38 -40, 59).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, proteasome activity recovers at the same rate with irreversible inhibitors as with slowly reversible inhibitors (27,36), presumably because of induction of de novo proteasome synthesis (37).…”
Section: Next-generation Proteasome Inhibitors In Clinical Developmentmentioning
confidence: 94%
“…The proteasome inhibitors in clinical development have the greatest potency for the CT-L active site of the proteasome (24,27,36,38,39), but they differ in their activity against the other catalytic sites. The development of compounds with different selectivity profiles will help address the question of what combination of proteasome site inhibition provides maximal antitumor effects and the best therapeutic index.…”
Section: Next-generation Proteasome Inhibitors In Clinical Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we investigated the stability of 2b, instead of 2a due to its poor solubility in aqueous medium, and demonstrated that 2b is gradually degraded in aqueous medium, while its half-life (t 1/2 = 10 h in pH 7.4 buffer) 14b is longer than that of other β-lactone-type proteasome inhibitors (omuralide, 13 min; salinosporamide A, 56 min). 17 Furthermore, it was found that 2b is significantly unstable under biological conditions (t 1/2 = 2.3 min in serum), which might be correlated with the relatively weak cell growth inhibitory effect of 2a, because 2a can be as unstable as 2b. Thus, we planned to develop stabilized derivatives of 2a.…”
Section: Introductionmentioning
confidence: 99%